Found this lovely identity the other day, and thought it was fun enough to share as a problem:

If $a+b+c=0$ then show $$\frac{a^3+b^3+c^3}{3}\frac{a^7+b^7+c^7}{7} = \left(\frac{a^5+b^5+c^5}{5}\right)^2.$$

There are, of course, brute force techniques for showing this, but I'm hoping for something elegant.

  • 1
    $\begingroup$ Why would somebody downvote this. I am upvoting it.. $\endgroup$ Feb 18, 2016 at 6:03
  • 2
    $\begingroup$ See math.stackexchange.com/questions/851985/… $\endgroup$ Feb 18, 2016 at 6:04
  • $\begingroup$ Nobody downvoted. @MarkFischler (Or if the did, they quickly retracted.) $\endgroup$ Feb 18, 2016 at 6:05
  • $\begingroup$ Nice, @labbhattacharjee ! $\endgroup$ Feb 18, 2016 at 6:06
  • 2
    $\begingroup$ @MarkFischler I accidentally downvoted it while meaning to press the favorite button. Sorry. $\endgroup$
    – S.C.B.
    Feb 18, 2016 at 6:09

7 Answers 7


Let $T_{m}$ be $a^m+b^m+c^m$.

Let $k=-ab-bc-ca$, and $l=abc$.

Note that this implies $a,b,c$ are solutions to $x^3=kx+l$.

Using Newton's Identity, note the fact that $T_{m+3}=kT_{m+1}+lT_{m}$(which can be proved by summing $x^3+kx+l$)

It is not to difficult to see that $T_{2}=2k$, $T_3=3l$, from $a+b+c=0$.

From here, note that $T_{4}=2k^2$ using the identity above.

In the same method, note that $T_{5}=5kl$.

From here, note $T_{7}=5k^2l+2k^2l=7k^2l$ from $T_{m+3}=kT_{m+1}+lT_{m}$ . Therefore, the equation simplifies to showing that $k^2l \times l=(kl)^2$, which is true.

  • $\begingroup$ Not clear why this answer has so few upvotes. It's definitely the easiest and least brute-force answer. Maybe if you were explicit about why $T_{m+3}=kT_{m+1}+lT_m$ - maybe spell out what $k,l$ are? (They look like "constants, since you use $k,l,m$, when what they really are is polynomials in $a,b,c$.) $\endgroup$ Feb 19, 2016 at 14:29
  • $\begingroup$ @Thomas Andrews Noted. Hope my edit clarifies matters. $\endgroup$
    – S.C.B.
    Feb 19, 2016 at 14:34
  • 3
    $\begingroup$ Perhaps people who are not comfortably familiar with Newton's identities look at this solution as pulling a rabbit out of a hat, and would not upvote it for that reason (although I am, because it throws light on the case I started looking at, with 4 variables). $\endgroup$ Feb 20, 2016 at 22:10

Useful identities:

$(y-z)^{3}+(z-x)^{3}+(x-y)^{3}= 3(y-z)(z-x)(x-y)$

$(y-z)^{5}+(z-x)^{5}+(x-y)^{5}= 5(y-z)(z-x)(x-y)(x^{2}+y^{2}+z^{2}-yz-zx-xy)$

$(y-z)^{7}+(z-x)^{7}+(x-y)^{7}= 7(y-z)(z-x)(x-y)(x^{2}+y^{2}+z^{2}-yz-zx-xy)^{2}$

By letting $a=y-z,b=z-x,c=x-y$.


Here's the symmetric polynomial approach.

$a^n+b^n+c^n$ is a symmetric homogeneous polynomial of degree $n$. So it can be expresses as a linear combination of polynomials $s_1^is_2^js_3^k$ where $i+2j+3k=n$, and $s_1=a+b+c,$ $s_2=ab+bc+ac,$ $s_3=abc$ are the elementary symmetric polynomials.

Now, $s_1=a+b+c=0$ implies that $a^n+b^n+c^n$ can be written as a linear combination of $s_2^js_3^k$ with $2j+3k=n$.

It the case where $n=2,3,4,5,7$, there is only one pair $j,k$ such that $2j+3k=n$, so $a^n+b^n+c^n$ becomes a monomial in $s_2,s_3$.

When $n=2$, this means $a^2+b^2+c^2=k_2s_2$ for some constant $k_2$. Setting $(a,b,c)=(2,-1,-1)$, we see $k_2=-2$.

When $n=3$, this means $a^3+b^3+c^3=k_3s_3$ for some constant $k_3$. Setting $a=2,b=c=-1$, we get $k_3=3$.

Similarly $a^5+b^5+c^5=k_5s_2s_3$, and again we use $(a,b,c)=(2,-1,-1)$ to get that $k_5=-5$.

Likewise, $a^7+b^7+c^7=7s_2^2s_3$.

Similar formula under the same condition:

$$\frac{a^2+b^2+c^2}{2}\frac{a^3+b^3+c^3}{3} = \frac{a^5+b^5+c^5}{5}\\ \frac{a^2+b^2+c^2}{2}\frac{a^5+b^5+c^5}{5} = \frac{a^7+b^7+c^7}{7} $$

More generally, if $a,b,c\in\mathbb Z$ with $a+b+c=0$ and $n$ is relatively prime to $6$ then $a^n+b^n+c^n$ is divisible by $s_2s_3=(ab+ac+bc)abc$.

There's actually an expression for $a^n+b^n+c^n$ with explicit coefficients:

$$a^n+b^n+c^n = \sum_{i+2j+3k=n} (-1)^j\frac{n}{i+j+k}\binom{i+j+k}{i,j,k} s_1^is_2^js_3^k\tag{1}$$

I confess I found that formula when looking at Fermat's Last many many years ago. It occurred to me at the time that Fermat can be expresses, for odd $n$, as

Given odd positive integer $n>1$. Then for integers $a,b,c$, $a^n+b^n+c^n=0$ if and only if $a+b+c=0$ and $abc=0$.

which seemed to imply it is a question about symmetric polynomials.

  • $\begingroup$ Nice, but what does $\binom{i+j+k}{i,j,k}$ mean? $\endgroup$
    – vesszabo
    Feb 28, 2016 at 14:14
  • $\begingroup$ It's a multinomial. @vesszabo $\endgroup$ Feb 28, 2016 at 18:39

Start off with the fact that $$a^2+b^2+c^2 = (a+b+c)^2 - 2(ab+bc+ca) = - 2(ab+bc+ca) $$

Since $a+b+c=0$ we know that ${a,b,c}$ are the three roots of some cubic missing the $x^2$ term: $$ x^3+kx+m = 0 $$ with $ab+bc+ca = k$. And by the way, that says that $$a^2+b^2+c^2=-2k$$

Now start chaining upward, expressing $a^n+b^n+c^n$ in terms of $m$ and $k$. For $n=3$ we add the cubic expression with $x=a$ to that with $x=b$ and $x=c$ to get $$ a^3+ b^3 + c^3 +k(a+b+c)+(m+m+m) = 0 \\ a^3+ b^3 + c^3 +3m = 0 \\ a^3+ b^3 + c^3 = -3m $$ Now for $n=4$ we multiply each of the equations by $a$, $b$ and $c$ respectively before adding them: $$ a^4+ b^4 + c^4 +k(a^2+b^2+c^2)+m(a+b+c) = 0 \\ a^4+ b^4 + c^4 -2k^2 = 0 \\ a^4+ b^4 + c^4 = 2k^2 $$ Now for $n=5$ we multiply each of the equations by $a^2$, $b^2$ and $c^2$ respectively before adding them: $$ a^5+ b^5 + c^5 +k(a^3+b^3+c^3)+m(a^2+b^2+c^2) = 0 \\ a^5+ b^5 + c^5 -3mk -2mk = 0 \\ a^5+ b^5 + c^5 = 5mk $$ For this problem we can afford to skip $n=6$. $$ a^7+ b^7 + c^7 +k(a^5+b^5+c^5)+m(a^4+b^4+c^4) = 0 \\ a^7+ b^7 + c^7 +5mk^2 +2mk^2 = 0 \\ a^7+ b^7 + c^7 = -7mk^2 $$ Then your identity reads $$ \left( -\frac{3m}{3} \right) \left( -\frac{7mk^2}{7} \right) = \left( -\frac{5mk}{5} \right)^2 \\ \left( -m \right) \left( -mk^2 \right) = (mk)^2 $$



The key here is the identity (for all $n\in\mathbb Z_{\ge 3}$):



Therefore: $$a^3+b^3+c^3=3abc\\ a^4+b^4+c^4=2(ab+bc+ca)^2\\ a^5+b^5+c^5=-5abc(ab+bc+ca)\\a^7+b^7+c^7=7abc(ab+bc+ca)^2$$


$$\frac{a^3+b^3+c^3}{3}\frac{a^7+b^7+c^7}{7} = \left(\frac{a^5+b^5+c^5}{5}\right)^2\\\frac{a^2+b^2+c^2}{2}\frac{a^3+b^3+c^3}{3}=\frac{a^5+b^5+c^5}{5}\\ \frac{a^2+b^2+c^2}{2}\frac{a^5+b^5+c^5}{5}=\frac{a^7+b^7+c^7}{7}\\$$


If we remember the well-known formulas

$(x+y)^3 - (x^3 + y^3) = 3xy(x+y)$

$(x+y)^5 - (x^5 + y^5) = 5xy(x+y)(x^2 + xy + y^2)$

$(x+y)^7 - (x^7 + y^7) = 7xy(x+y)(x^2 + xy + y^2)^2$

then your identity becomes the observation that there are equal powers of the $xy(x+y)$ and $(x^2+xy+y^2)$ factors on both sides. (Under the change of notation $a,b,c \to -(x+y),x,y$)

  • $\begingroup$ This solution makes the problem clear, and easy to remember. $\endgroup$
    – orangeskid
    Sep 21, 2021 at 5:24

Let $a,b,c$ be roots of $$x^3+mx-n=0$$
From Vieta formula we get: $$ 0 = (a+b+c)^2 = a^2+b^2+c^2+2m$$ so $$\boxed{a^2+b^2+c^2 =-2m}$$ Further $$x^3 = n-mx\implies a^3+b^3+c^3 = 3n-m(a+b+c) =3n $$ so $$\boxed{a^3+b^3+c^3 =3n}$$

Also $$x^5 = nx^2-mx^3 = nx^2-mn+m^2x$$ so $$a^5+b^5+c^5 = n(a^2+b^2+c^2)-3mn = -5mn$$ so $$\boxed{a^5+b^5+c^5 =-5mn}$$

Finally $$x^7 = x(n-mx)^2 = n^2x-2mnx^2+m^2x^3 $$ $$=n^2x-2mnx^2+m^2n-m^3x$$ so $$\boxed{a^7+b^7+c^7 = 7m^2n}$$

and we are done.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.